ECONOMIC EMPOWERMENT THROUGH COLLABORATION AND BUSINESS INNOVATION IN IMBI VILLAGE, JAYAPURA - Mas'ud, Marwah; Ditilebit, Nobertha (TOPLAMA, 2024)
This study aims to empower the economy of the community in Kelurahan Imbi, Jayapura, through collaboration and business innovation using the Participatory Action Research (PAR) method. The PAR approach involves active community participation in every stage of the research, from problem identification to solution implementation and evaluation. Problem identification was carried out through focus group discussions and in-depth interviews, revealing various challenges such as limited access to capital, low levels of education and skills, poor infrastructure, and a lack of collaboration among stakeholders. Based on these findings, an action plan was formulated, including business financing programs, skills training and business mentoring, infrastructure improvements, and strengthening collaboration. The program implementation was conducted with active community involvement. The research results showed an increase in business actors' access to capital through low-interest loan schemes and savings and loan cooperatives. Training and business mentoring successfully enhanced community knowledge and skills, and encouraged product innovation and digital marketing. Infrastructure improvements increased mobility and market access, while the collaborative forum among stakeholders strengthened synergy and the effectiveness of economic empowerment programs. In conclusion, the PAR approach is effective in empowering the economy of the Kelurahan Imbi community, creating targeted and sustainable solutions, and building community capacity to develop local economic potential. This success underscores the importance of community participation and stakeholder collaboration in creating sustainable socio-economic change.